2013
DOI: 10.1007/s13224-013-0457-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Training of Traditional Birth Attendants on Maternal Health Care: A Community-based Study

Abstract: Training programme for TBAs with regular follow-ups in the resource-poor setting will not only improve the quality of maternal care but also reduce perinatal deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
3
6
0
Order By: Relevance
“…Despite these challenges of the audio-visual workshop intervention, its effect on knowledge was statistically signi cant across the zones and in the total population of TBAs. This further emphasizes that, effective training of TBAs with appropriate materials can improve knowledge as similarly reported in other studies with training interventions, where knowledge had resulted in improved maternal and neonatal outcomes [12,17,18,21].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Despite these challenges of the audio-visual workshop intervention, its effect on knowledge was statistically signi cant across the zones and in the total population of TBAs. This further emphasizes that, effective training of TBAs with appropriate materials can improve knowledge as similarly reported in other studies with training interventions, where knowledge had resulted in improved maternal and neonatal outcomes [12,17,18,21].…”
Section: Discussionsupporting
confidence: 72%
“…The training of TBAs in the conventional maternal health-care delivery systems, has shown to increase the utilization of health facility's prenatal, antenatal and postnatal care services which invariably improves maternal and neonatal health [12]. Empowerment, a consequence of effective training is an intentional process, centered in local communities involving active participation, critical re ection, awareness, understanding and control over decisions [13].…”
Section: Introductionmentioning
confidence: 99%
“…While the WHO has specifically excluded TBAs from their recommendation for skilled attendance at birth, they can play a valuable role where skilled care is available but underutilized, by serving as liaisons between rural women and health providers due to their existing social and cultural importance [23]. Training TBAs to provide prenatal and postpartum care, to recognize warning signs of pregnancy complications during delivery, and when to refer a woman to a health provider has the potential to improve maternal and newborn health outcomes in Nepal [24].…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] A study conducted in India among trained and untrained TBAs found that 64% of untrained TBAs felt it was important for women to receive antenatal care services (ANC). [ 24 ] Additionally, over 80% of trained TBAs and 60% of untrained TBAs in the study expressed that safe delivery practices will reduce maternal and infant deaths.…”
Section: Resultsmentioning
confidence: 99%